Uncontrolled risk the lessons of Lehman Brothers and how systemic risk can still bring down the world financial system - Williams, Mark T. 1963- (McGraw-Hill, 2010)
A risk advisor for top financial institutions explains how limitless risky behaviors toppled a 158-year-old institution, using the story to illuminate the interconnection of the global financial system, as well as broader policy implications